(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Narrowband (NB) UVB phototherapy is considered practically to be an effective and safe modality as compared to other systemic therapies and Broad band UVB phototherapy for management of psoriasis. The objective of the study was to determine the efficacy of narrowband UVB in chronic plaque psoriasis in skin type IV and V. Patients & Methods: A Qausi experimental study was carried out in Dermatology Department, Sahiwal Teaching Hospital, for one-year duration from March 2022 to February 2023. Patients of both gender and age between 16 and 65 years were included. All the patients were exposed to thrice weekly sessions of narrowband UVB with starting dose of 280mj with 10 % increment weekly. Efficacy was assessed at baseline and then at 4th, 8th and 12th week by PASI (Psoriatic Area and Severity Index). All research data was noted on predesigned proforma and was analyzed by using SPSS version 26. Results: Thirty-one patients were enrolled with male to female ratio of 23:8. The baseline mean PASI score was 16.62±6.03, and it significantly decreased to 2.77±1.70 after the 12-week follow-up, indicating the effectiveness of NUVB phototherapy in the treatment of chronic plaque psoriasis (P-value<0.05). Pruritus 22.6 %(n=7) was the common side effects noted followed by painful erythema 9.7 %(n=3). Conclusion: Narrowband UVB has demonstrated to be effective and safe therapy in the treatment of psoriasis. This therapy typically results in fewer side effects.